2023
DOI: 10.1038/s41419-023-06104-4
|View full text |Cite
|
Sign up to set email alerts
|

Ficolin B secreted by alveolar macrophage exosomes exacerbates bleomycin-induced lung injury via ferroptosis through the cGAS-STING signaling pathway

Xu Wu,
Yixia Jiang,
Rong Li
et al.

Abstract: Pathogenesis exploration and timely intervention of lung injury is quite necessary as it has harmed human health worldwide for years. Ficolin B (Fcn B) is a recognition molecule that can recognize a variety of ligands and play an important role in mediating the cell cycle, immune response, and tissue homeostasis in the lung. However, the role of Fcn B in bleomycin (BLM)-induced lung injury is obscure. This study aims to investigate the sources of Fcn B and its mechanism in BLM-induced lung injury. WT, Fcna-/-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Activation of α-SMA has been considered to play a critical role in pulmonary fibrosis. Higher concentrations of total protein in BALF, the levels of hydroxyproline and expression of α-SMA are concurrent with more collagen deposition, inducing more severe pulmonary fibrosis [ 33 , 34 ]. It has been revealed that there is a strong relationship between the extent of the fibrosis and the MMP‐9 levels, indicating that MMP‐9 plays a crucial role in the pathogenesis of pulmonary fibrosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of α-SMA has been considered to play a critical role in pulmonary fibrosis. Higher concentrations of total protein in BALF, the levels of hydroxyproline and expression of α-SMA are concurrent with more collagen deposition, inducing more severe pulmonary fibrosis [ 33 , 34 ]. It has been revealed that there is a strong relationship between the extent of the fibrosis and the MMP‐9 levels, indicating that MMP‐9 plays a crucial role in the pathogenesis of pulmonary fibrosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…by selecting WT, Fcna−/− and Fcnb−/− mice to construct bleomycin (BLM)-induced lung injury model, found that Ficolin B (Fcn B), which is transported by AMs exosomes, promotes ferroptosis of lung epithelial cells through cGAS-STING signaling pathway, thus aggravating BLM-induced lung injury. 101…”
Section: Application Of Ferroptosis-based Nanomedicine Delivery Syste...mentioning
confidence: 99%
“…[ 68 ] Moreover, ferroptosis was also proved to be responsible for PM2.5-mediated pulmonary fibrosis and heavy metals-induced pulmonary fibrosis. [69,70] To our knowledge, several ferroptosis pathways associated with pulmonary fibrosis have been revealed, including NCOA4-mediated ferritinophagy, [ 71 ] miR-150–5p/ SLC38A1 signaling, [ 72 ] Keap1/Nrf2 signaling, [ 73 ] cGAS/ STING signaling, [ 74 ] Nrf2/HO-1 signaling, [ 75 ] Wnt5a/Ca 2+ signaling, [ 76 ] USP3/Sirt3/p53 signaling, [ 77 ] EMPA/Nrf2/ SLC7A11 signaling, [ 78 ] and ACSL4-dependent ferroptosis pathway ( Figure 3B ).…”
Section: Pulmonary Fibrosismentioning
confidence: 99%